2006
DOI: 10.1007/s00296-005-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic evidence of subclinical atherosclerosis obtained by carotid ultrasonography in patients with Behcet’s disease

Abstract: Subclinical atherosclerosis can be demonstrated by measuring the intima-media thickness (IMT) of the carotid arteries by high-resolution B-mode ultrasonography (US). Endothelial injury appears a key event in the atherogenesis. Endothelial cell activation and/or injury are the characteristic features of Behçet's disease (BD). In this study, we investigated morphologic evidence of subclinical atherosclerosis in the BD patients by using high-resolution B-mode US. Thirty-four patients with BD without arterial invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
5
17
1
Order By: Relevance
“…[2,15] Endothelial dysfunction occurs before visible structural changes of the arterial wall [7] and represents a key event in subclinical atherosclerosis in BD. [16] Our study showed that IMT increases in patients with hepatitis. The development of atherosclerosis has an inflammatory component; however, it is not clear whether hepatitis B and C viral infections are associated with the risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 75%
“…[2,15] Endothelial dysfunction occurs before visible structural changes of the arterial wall [7] and represents a key event in subclinical atherosclerosis in BD. [16] Our study showed that IMT increases in patients with hepatitis. The development of atherosclerosis has an inflammatory component; however, it is not clear whether hepatitis B and C viral infections are associated with the risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 75%
“…An increased degree of endothelial cell injury and pathological activation has been reported in BD, with studies showing elevated levels of endothelial injury markers like soluble thrombomodulin, von Willebrand factor, and circulating E-selectins associated with this disease [12]. Recent studies have also shown a higher prevalence of carotid atherosclerotic plaques and increased carotid intimal thickening in patients with BD, further suggesting that these patients have an increased burden of subclinical atherosclerosis [13]. This is mediated by increased oxidative stress-related endothelial dysfunction in these subjects [14].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][21][22][23][24][25][26] Increased values of IMT with BD have been reported in some studies. [7][8][9] Alan et al [8] also proved the existence of decreased arterial distensibility in BD, and Rhee et al [22] detected increased arterial stiffness in BD. Akçar et al [26] reported lower peak systolic and end-diastolic flow velocities throughout internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Many authors have proven that inflammation is also an independent risk factor for this disease. [3][4][5][6][7][17][18][19] Indeed, ECD can be demonstrated in more than one vascular bed, and this is related to focal inflammation. Suppression of the immune inflammatory process may result in the reversal of ECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation